1989
DOI: 10.1111/j.1365-2621.1989.tb07911.x
|View full text |Cite
|
Sign up to set email alerts
|

1H and 23Na NMR Relaxation Studies of the NaCl/β‐Lactoglobulin System Equilibrated at Various Water Activities

Abstract: NMR relaxation times (T,) of 'H and 2"Na were determined at 8, 14, 60, MHz and at 14,52 MHz, respectively, in the NaCI/@lactoglobulin system equilibrated at water activities ranging from 0.11 to 0.97. A two-state model was used for both nuclei which allowed the calculation of proportions of bound and free species. It was shown that bound water and Na+ increased at medium water activities in the presence of increasing NaCI. The discrepancy with adsorption isotherms data was explained by (1) limitations of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…It is characteristic of inorganic or organic porous materials. A similar pattern was found in previous food science studies focusing on model molecules such as casein, lactoglobulin (Fanni et al, 1989;Curme et al, 1990) or on more heterogeneous material such as meat (Kabil et al, 2012). Plant litter's ability to adsorb water is a property of huge importance, enhancing habitat conditions for plants, micro invertebrates and microorganisms in litters and soils (Henry, 2012;Kammer et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is characteristic of inorganic or organic porous materials. A similar pattern was found in previous food science studies focusing on model molecules such as casein, lactoglobulin (Fanni et al, 1989;Curme et al, 1990) or on more heterogeneous material such as meat (Kabil et al, 2012). Plant litter's ability to adsorb water is a property of huge importance, enhancing habitat conditions for plants, micro invertebrates and microorganisms in litters and soils (Henry, 2012;Kammer et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…The threshold found (a w ¼ 0.75) can be explained by the fact that below this value, NaCl crystallizes and can no longer adsorb water molecules. Previous studies (Curme et al, 1990;Fanni et al, 1989) showed that when NaCl was added to proteins such as casein or blactoglobuline, NaCl ceased to adsorb water below a w ¼ 0.75, actually turning into a crystal. The findings here are of importance, demonstrating that exposure to NaCl (from 35 g.L À1 ) aggravates matric stresses (due to desiccation) in litters above a certain a w threshold (0.75), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy has proved to be an excellent method to study the chemical state of ions, as reflected in the longitudinal relaxation time ( T 1 ) and transverse relaxation time ( T 2 ) 7. 8 23 Na NMR has been widely used, for example, to determine salt mobility in food or model systems9, 10 and to determine the perception of saltiness in salty gum solutions 1112.…”
Section: Introductionmentioning
confidence: 99%